Advanced Holography Metrology and Imaging - Naydenova, Izabela (IntechOpen, 2011)
Advanced Holography - Metrology and Imaging covers digital holographic microscopy and interferometry, including interferometry in the infra red. Other topics include synthetic imaging, the use of reflective spatial light modulators for writing dynamic holograms and image display using holographic screens. Holography is discussed as a vehicle for artistic expression and the use of software for the acquisition of skills in optics and holography is also presented. Each chapter provides a comprehensive introduction to a specific topic, with a survey of developments to date.